Artificial Intelligence Waves on Space Computation Management: A Review Report - Rahman, Mostafijur; Amin, Ruhul (Engineering International, 2020)
When writing about the history of the internet, it is important to note that aerospace was among the significant pioneers in computer networking computer network for private was used in first airline reservation system “SABRE” in 1960 for American airlines. While sage was the first computer system in the world, its deficiencies led to the development of ARPANET. These systems formed the foundations for the internet and the development of other computer programs in aerospace, any deficiency led to the invention of a new program, giving birth to programming, CAD, and CAM that brought about simulations. Aerospace computing has evolved over the years and is now carrying the whole weight of the aerospace industry. Before the launch of any space vehicle or satellite, simulation has become a necessary step, checking for weaknesses for corrections to be done on the ground. Besides, computer simulation has been essential in training, facilitating the training of pilots worldwide. This article presents more information regarding the application of AI in aerospace computing, flight simulations, and their advantages in the aerospace industry.